(3TQM JSgjd GdahGFO hJcejd GdebGUOs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3hHYO, agPG JYdjb Ydi JSgjd GdahGFO hJcejd GdebGUO CYajJg ef GdEcKGQ, hedJ ajg Edi GdGNJUGQ s
(3BNQgG (B:s
(3Hd ef HGH eG Ef jJYOi Edi hGMO hGddg CYde Je GdLRA GdChd ef TQM GdJSgjd jJdhg aj GdKGfj HGH GSe GdaGYd s
(3JYGhQ YdjgG fGSNGfs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B167 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B406s
Keywords: (3GdfMhs